Perpinsahan Desa Mruwak Berdasarkan Prasasti Mrwak (1108 Śaka/1186 M) - Churmatin Nasoichah (Berkala Arkeologi Sangkhakala, 2008)
AbstractThe tragedy of war is one aspect which contained in some inscriptions. In the other side,it has a very bad effect for the people themselves, e.g. removeling a village location. That event have a direct impact to the life’s pattern which has an interconnection with the environment and their livelihood changing